Analysis of organic content on sediment and mangrove density in mangrove conservation area, Mamburungan urban village, Tarakan city, Indonesia - Imra Imra; Minawati Minawati; Abdul Jabarsyah (Universitas Muhammadiyah Malang, 2022)
The mangrove ecosystem in Mamburungan Village is known to have two dominant types of mangroves, namely Avicennia sp. and Sonneratia sp. The main factors that cause mangrove growth zoning are the type of substrate and the content of organic matter. This research was conducted through several stages, namely, determining the location, preparing tools and materials, taking sediment, and analyzing mangrove data. The highest organic matter content was found at station I of 2.53 % - 17.81 %, and the highest mangrove density ranged from 0.05 ind m-2 - 0.12 ind m-2 which was dominated by Avicennia sp. More organic matter content was found at a depth of 0 cm.